Mutual interaction between YAP and CREB promotes tumorigenesis in liver cancer. Issue 3 (16th July 2013) - Wang, Jiayi; Ma, Lifang; Weng, Wenhao; Qiao, Yongxia; Zhang, Yue; He, Jiangtu; Wang, Hongmei; Xiao, Weifan; Li, Lanlan; Chu, Qinghua; Pan, Qiuhui; Yu, Yongchun; et al.
<x xml:space="preserve">Abstract</x> Yes‐associated protein (YAP), the downstream effecter of the Hippo‐signaling pathway as well as cyclic adenosine monophosphate response element‐binding protein (CREB), has been linked to hepatocarcinogenesis. However, little is known about whether and how YAP and CREB interact with each other. In this study, we found that YAP‐CREB interaction is critical for liver cancer cell survival and maintenance of transformative phenotypes, both in vitro and in vivo. Moreover, both CREB and YAP proteins are highly expressed in a subset of human liver cancer samples and are closely correlated. Mechanistically, CREB promotes YAP transcriptional output through binding to −608/−439, a novel region from the YAP promoter. By contrast, YAP promotes protein stabilization of CREB through interaction with mitogen‐activated protein kinase 14 (MAPK14/p38) and beta‐transducin repeat containing E3 ubiquitin protein ligase (BTRC). Gain‐of‐function and loss‐of‐function studies demonstrated that phosphorylation of CREB by MAPK14/p38 at ser133 ultimately leads to its degradation. Such effects can be enhanced by BTRC through phosphorylation of MAPK14/p38 at Thr180/Tyr182. However, YAP negatively controls phosphorylation of MAPK14/p38 through inhibition of BTRC expression. Conclusion: There is a novel positive autoregulatory feedback loop underlying the interaction between YAP and CREB in liver cancer, suggesting that YAP and CREB form a nexus to integrate the protein kinase A, Hippo/YAP, and MAPK14/p38 pathways in cancer cells and thus may be helpful in the development of effective diagnosis and treatment strategies against liver cancer. (Hepatology 2013;53:1011–1020)